Evaluation of storability of some onion cultivars planted at different densities under the condition of Al-Gabel Al-Akhder region - Gad-Allah, Soliman Omar; Mohamed, Saleh Abd EL-Rehim; Abd EL-Wahed, Ahmed Mohamed Ahmed (Al-Mukhtar Journal of Sciences, 2008)
Six onion varieties were evaluated under four planting spaces at the experimental farm of Faculty of Agriculture, Omar Al-Mokhtar University, Al-Beida, Al-Gabal Al-Akhdar region, during the two successive seasons of 2006 and 2007. The tested varieties were Red Amposta , El-Behairy, Red Creole, Giza 20, Giza 6 and Texas Early Grano. Plant densities between seedlings were 7.5, 10, 12.5 and 15cm, which equal 532,400,320,126 thousands seedlings per hectar,respectively.     The six varieties, four spacings, two storage methods and their various interactions were compared in respect to the storage ability of  bulbs for six monthes under room and cold storage conditions  at zero 0˚c.                The obtained results could be summarized as follow:Cold storage significantly depressed the percentages of weight loss, sprouting and rot as compared to the ambient temperature (room storage).The percentages of bulb weight loss and bulb rot were increased by increasing plant spacing, especially when comparing the 7.5 with 15 cm at all storage periods.The 7.5cm spacing was the best, for decreasing the percentage of sprouted bulbs, at all storage periods in the two seasons.After 180 days of storage bulbs of Red Amposta variety recorded the lowest percentages of weight loss (7.73%), sprouting (6.40%) and rot (3.28%) . On the other hand, Red Creole recorded the highest weight loss (12.48%) and sprouting (88.59%), but the bulbs of Giza 6 and Giza 20 recorded the highest percentage rot (18.13%) .Increasing the distance up to 12.5 cm in cold storage, and up to 15 cm in room storage increased the weight loss percentage.The distances of 7.5 cm and 10.0 cm were the best for decreasing sprouting percentage in room and cold storage, respectively. The wider distances, increased sprouting percentage in both storage methods.Increasing the distance between plants, increased the percentage of bulb rot, either stored in ambient or in cold temperature at all storage periods, in both seasons, especially when comparing with the distances of 7.5 and 15 cm.Cold storage exceeded room storage in concern bulb weight loss at all storage periods. The tested varieties varied in their responce according to period and methods of storage.No significant difference in sprouting percentage of bulbs stored in ambient or• cold temperature for varieties of Red Amposta, El-Behairy, Giza 6 and Giza 20 at different storage periods, in two seasons, as well as for Texas Early Grano and Red Creole at 120 days, in second season.• The storage methods had no significant effect on the percentage of bulb rot of varieties of Red Amposta, El-Behairy and Red Creole, in both seasons, whereas the remained varieties were affected by storage methods.• There is relative differences within varieties regarding the response of stored bulbs to weight loss with varying planting distance, storage periods and studied seasons.• Plant spacings had no significant effect on sprouting of Red Amposta, till the end of storage period (180 days); Giza 6 ,till 150 days and Giza 20, till 120 days of storage, whereas the other varieties were affected by plant spacings.• Plant densities had no effect on the percentage of bulb rot of Red Amposta, Giza6 and Texas Early Grano, at all storage periods as well as on the varieties of El-Behairy and Giza 20 ,at 150 days of storage, whereas,the remained varieties were affected by plant distances.• The distance of 10 cm was the partner factor in decreasing sprouting percentage of all varieties, except Giza 6, in both ambient and cold temperature storage.• Plant distances had no effects on both bulb rot and sprouting of Red Amposta in cold and ambient temperatures as well as weight loss in cold storage, whereas, 7.5 cm. was the best in ambient temperature.• Plant distances had no effect ,in both seasons, on bulb rot and in the second season, on sprouting of Texas Early Grano till 150 days in cold storage and till 120 days in ambient temperature. whereas, in first season, 10 cm was the best for reducing sprouting percentage. Moreover, the distance of 7.5 was favourable for reducing weight loss in both cold and ambient temperature, although no differed significantly, sometimes, with 12.5 or 15 cm.